MEDIA DARING BERBASIS ANDROID DALAM MENINGKATKAN KEMAMPUAN MEMBACA PADA PEMBELAJARAN DI MIN 1 LABUHANBATU UTARA - Hairullah, Hairullah; Napitupulu, Dedi Sahputra; Siregar, Yus Erlina Effendi (STIT Al-Ittihadiyah Labuhanbatu Utara, 2024)
The aim of this research is to describe Android-based online media in improving reading skills in learning at MIN 1 North Labuhanbatu. This research method uses qualitative research methods with interviews, observation and documentation. The findings in this research are the use of WhatsApp as a learning medium in the network during the Covid-19 pandemic by class teachers. Teachers use photo, video, document, WhatsApp Group and direct call (telephone) features. Convenience is felt with the presence of the WhatsApp feature and also its easy use and can be used by various groups. Parents' supervision of children when learning to use cellphones and unstable networks can hinder the learning process. However, there are many solutions that can be done to continue online learning by using WhatsApp groups so that the learning process can run smoothly and students don't feel bored and students can understand the learning.